Aplikasi arang aktif tempurung kemiri sebagai komponen media tumbuh semai melina - Mody Lempang; Hermin Tikupadang (Foresty Faculty of Hasanuddin University, 2013)
Application of activated charcoal in agriculture will give advantage for plant growth because will enrich nutrients, mantain soil properties, enhance root development and increase microorganism propagation and activities that would support the plant growth. The objective of this research is to examine the effect of Candlenut shell activated charcoal addition into culture medium on seedling growth of Gmelina arborea Roxb. Candlenut shell (Aleurites moluccana Willd) was carbonised in drum kiln to produce charcoal, then the charcoal was activated in electrical retort which generates steam with heating duration of 120 minutes at temperature of 7500 C. The activated charcoal was applied into culture medium of G. arborea seedling with concentration of 5, 10 and 15% by weigth of culture medium. The results showed that addition of the activated charcoal into culture medium significantly increased heigth, stem diameter and biomass dryweigth of G. arborea seedling. The addition of 15% activated charcoal into the culture medium has given the best results with the increased heigth, stem diameter and biomass dryweigth respectively 8.2, 45.95 and 58.82%.